Multinational Corporation’s Investments made through its Subsidiary under The Latest Generation of Investment Treaties - Amalia, Prita; Makmun, M. Lazuardy Thariq (Indonesian Journal of International Law, 2021)
Multinational Corporation (MNC) influence and contribution in the world’s economic development, particularly in the realm of international investment is vast and inevitable. The way MNC utilizes its subsidiaries however, has posed an issue for host States specifically in relation with the serial of ISDS claims which is faced by host States. Where the structure of MNC’s investment enables them to go ‘treaty-shopping’. It is understood that there is a causality between the broad definition of investment and investor contained in the older generation of BITs toward these series of claims. It is also more often than not, in the case of an investment that was made through a subsidiary company, arbitral tribunals will accept such investment as an investment that is protected under the relevant BIT due to how investment and investor are defined. Consequently, it has put a considerable amount of concern to host States and in response, States are now starting to move forward to a new generation of BITs with a hope that it could give more clarity and certainty compared to the previous generation of BITs, particularly in regard with the definition of investment and investor. Questions arise on whether it really brings more clarity and certainty in terms of an investment that was made through a subsidiary? This article will analyze the impact of the newly tailored definition clause under the latest generation of BITs toward an investment that is conducted through a subsidiary including the legal standing of the investor therein.